Laboratory comparison of new high flow rate respirable size-selective sampler. Issue 10 (3rd October 2018) - Lee, Taekhee; Thorpe, Andrew; Cauda, Emanuele; Tipton, Leah; Sanderson, Wayne T.; Echt, Alan
Abstract: A newly developed high flow rate respirable size-selective cyclone sampler (GK4.162—also known as the Respirable Air Sampling Cyclone Aluminum Large (RASCAL)) was calibrated to determine its optimum operating flow rate. The Health and Safety Laboratory in the United Kingdom and two laboratories from the National Institute for Occupational Safety and Health in the United States conducted experiments using two different methods: (1) polydisperse aerosol and time-of-flight direct reading instrument (Aerodynamic Particle Sizer (APS)) and (2) monodisperse aerosol and APS. The measured performance data for the cyclone was assessed against the international respirable convention using the bias map approach. Although the GK4.162 cyclone was tested using different aerosols and detection methods, the results from the three laboratories were generally similar. The recommended flow rate based on the agreement of results from the laboratories was 9.0 L/min.